Association between herpes zoster and Parkinson’s disease and dementia: a systematic review and meta-analysis - Zhang, Yanfeng; Liu, Weiping; Xu, Yang (Frontiers in Neurology, 2024)
ObjectivesThis meta-analysis investigated the relationship between herpes zoster and the risk of dementia or Parkinson’s disease by analyzing published clinical studies.MethodsWe systematically searched PubMed, Cochrane, Embase, and Web of Science Core Collection databases on April 25, 2024. Hazard ratios (HR) were used for statistical analyses. Random-effects models were applied, and heterogeneity was assessed using the I2 statistic.ResultsHerpes zoster was associated with a non-significant trend toward increased dementia risk (HR = 1.11, 95% CI 0.99–1.24, p = 0.07) but significantly increased Parkinson’s disease risk (HR = 1.15, 95% CI 1.03–1.30, p = 0.02). Subgroup analyses revealed that herpes zoster significantly elevated the risk of the prospective study subgroup (HR = 1.08, 95% CI 1.02–1.13, p = 0.004) and vascular dementia subgroup (HR = 1.17, 95% CI 1.00–1.37, p = 0.05). Significant heterogeneity was observed for both outcomes (dementia: I2 = 98%, p < 0.00001; Parkinson’s disease: I2 = 94%, p < 0.00001).ConclusionHerpes zoster raises the risk of Parkinson’s disease and vascular dementia, with a potential causal link to dementia. Early vaccination against herpes zoster is recommended over post-infection antiviral treatment to mitigate risks.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/ and our registration number is CRD42024555620.